Voice training induced spontaneous pneumothorax - Akinmade, Akinola (Respir Med Case Rep, 2020)
BACKGROUND: Voice training induced spontaneous pneumothorax is seldom reported in the literature. This study reports a case of middle-aged man without comorbidities who presented with spontaneous pneumothorax following voice training and made a complete recovery after CT guided needle thoracostomy. CASE REPORT: This is a case of a middle-aged male non-smoker with ectomorphic build who presented with chest pain of sudden onset and difficulty in breathing following voice training. The chest pain was central, radiated to the left shoulder and aggravated by lying supine. Chest auscultation revealed reduced breath sounds on the left middle and lower lung zones posteriorly. An initial diagnosis of chest pain of unknown origin was made. Chest radiograph done revealed a left sided pneumothorax, with no background lung pathology seen. Chest CT was done to rule out any underlying pathology, to quantify the pneumothorax and to plan for CT guided needle thoracostomy at our institution. Complete resolution of the left sided pneumothorax was seen after the procedure. CONCLUSION: Voice training is a rare cause of primary spontaneous pneumothorax. In the absence of any other lung pathology, it can be effectively managed by CT guided needle thoracostomy as seen in the index patient. It is essential for emergency physicians to include voice training as a potential cause for primary spontaneous pneumothorax.